Treatment Strategies in Adult Dysphagia - Rita Kantanavičiūtė-Petružė; Saulė Grigaliūnaitė (Lithuanian Sports University, 2022)
Background. Swallowing disorders are becoming more common in an aging society, so it is important to understand and know the phases of swallowing, including the voluntary and involuntary aspects of the swallowing process, in order to be able to apply strategies to overcome swallowing disorders. Aim. To reveal the strategies in adult dysphagia treatment. Methods. Theoretical scientific research. This method enables to reveal and analyse the concept of swallowing disorders in the context of Lithuania and foreign countries, analyzes the variety of rehabilitation strategies applied to overcome swallowing disorders, and emphasizes the importance of complex dysphagia assessment and treatment. Adult dysphagia treatment strategies are compared and summarized. Results. The analysis of Lithuanian and foreign science research showed that complex strategies are most often applied for adult dysphagia treatment. Rehabilitative dysphagia treatment strategies are used to accelerate the recovery of swallowing function, and compensatory strategies are applied to ensure patient safety during eating. Conclusion. In each case, speech therapy differs depending on individual personal and external factors that affect swallowing disorder. Adult dysphagia treatment is usually complex in Lithuania: both rehabilitative and compensatory models are applied in dysphagia treatment. Keywords: swallowing disorders, dysphagia treatment strategies, rehabilitative dysphagia treatment strategies, compensatory dysphagia treatment strategies.